(untitled) - Gnap, Jozef; Cyprich, Ondrej (Doprava a spoje, 2010)
The paper deals with unevenness of passenger demand for transportation within Bardejov public transport system. Authors describe the process of obtaining and editing the input data and creating regression models of seasonal patterns. Finally they analyze passenger demand development of working and weekend days.